2020
DOI: 10.21203/rs.3.rs-136161/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Hub Genes Associated With Clinical Characteristics and Potential Therapy of Diabetic Nephropathy by Bioinformatics Analysis.

Abstract: Background: To provide molecular markers and potential targeted molecular therapy for diabetic nephropathy by screening hubgenes based on bioinformatic analysis. Results: We found 91 differentially expressed genes (DEGs) between diabetic nephropathy tissues and normal kidney tissues. Majority DEGs were significantly enriched in the extracellular matrix structural constituent, collagen-containing extracellular matrix. KEGG pathway analysis showed that most of DEGs participated in PI3K-Akt signaling pathway, AGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
1
0
0
Order By: Relevance
“…By means of LASSO regression analysis, the TXN, PHLDA2, RPLP1, MT1G, and SDC4 genes were identi ed and incorporated into a predictive model that exhibited robust diagnostic e cacy and remarkable stability. Xu et al utilised transcriptome sequencing datasets of DFU for analysis and revealed that TXN is the hub gene associated with the wound-healing process of DFU [31]. This nding aligns with the outcomes of our study.…”
Section: Expression Of Key Genes In Single Cellssupporting
confidence: 91%
“…By means of LASSO regression analysis, the TXN, PHLDA2, RPLP1, MT1G, and SDC4 genes were identi ed and incorporated into a predictive model that exhibited robust diagnostic e cacy and remarkable stability. Xu et al utilised transcriptome sequencing datasets of DFU for analysis and revealed that TXN is the hub gene associated with the wound-healing process of DFU [31]. This nding aligns with the outcomes of our study.…”
Section: Expression Of Key Genes In Single Cellssupporting
confidence: 91%